(untitled) (Itinera, 2021)
This article proposes connections between literature and science through the relatively recent scientific concept of chaos. I examine Laurence Sterne’s The Life and Opinions of Tristram Shandy, Gentleman and Denis Diderot’s Jacques the Fatalist and His Master to show how these authors contradict the scientific thinkers of their time by creating narrative structures that disrupt the normal flow of time and bend the typically absolute space between reader and fictional story. Though the physical books of Jacques and Tristram Shandy have a final page, the two authors leave it to their readers to finish the stories for themselves. The narrators of both novels interact with their readers, creating a space that allows their audience to fill in the narrator’s and author’s blanks. In doing this, these texts become simultaneously complete and incomplete. Thus, a narrative styled similarly to the thought experiment of Schrodinger’s cat is created. In this sense these novels can be perceived as precursors to scientific thought of the twentieth and twenty-first century.